Effectiveness of ultra-rapid dose titration of clozapine for treatment-resistant bipolar mania: case series. (August 2015) - Aksoy Poyraz, Cana; Turan, Şenol; Demirel, Ömer Faruk; Usta Sağlam, Nazife Gamze; Yıldız, Nazım; Duran, Alaattin
Treatment of severe and refractory manic episodes in hospital settings can occasionally be very difficult. In particular, severely excited patients showing aggressive, hostile, impulsive behaviours frequently require physical restraint and seclusion, high doses of antipsychotics and benzodiazepines, and sometimes, electroconvulsive therapy. Hospital stay is generally prolonged and such patients cause great emotional distress for other patients in the ward and clinical staff involved in their care. Here we report on three patients with a diagnosis of bipolar disorder and one patient with a diagnosis of schizoaffective disorder bipolar subtype, all of whom were hospitalized for severe manic episodes with psychotic features. These patients were extremely difficult to manage in the ward as no response could be obtained in the first week of treatment despite high doses of antipsychotics and benzodiazepine administration. The introduction and rapid titration of clozapine proved remarkably effective and was well tolerated in the acute management of these patients. We observed that clozapine had a superior and fast mood stabilization effect with rapid titration and could be extremely helpful in the management of such patients.